Application of psychoanalysis theory in personal counseling to improve the ego function of Junior High School students - Fitratul Ilmi Fajri; Yeni Karneli (Consilium, 2021)
The application of ego counseling is a counseling approach that emphasizes the function of the ego. This research is motivated by the weak function of the ego that is owned by students at this time, while it is the ego that develops everything. For example, the ability of students, their circumstances, social relationships and the distribution of their interests. A student must have a healthy and strong ego to respond to environmental conditions as a process of adapting. The research method used is an experimental research method . The sample in this study was class VIII students at MTs , while for the research design, the researcher used the pre-experimental method. with the type used is a one-group pretest-posttest design. M using an experimental quantitative approach. In this study, students of class VIII who have a low ego function. Based on the findings above, it can be concluded that there is an increase in ego function in students after being given individual counseling services using psychoanalytic theory.